Aplikasi probiotik dengan bahan lokal untuk meningkatkan pertumbuhan dan tingkat kelangsungan hidup Bawal air tawar (Colossoma macropomum) - Saselah, Jetti T.; Mandeno, Jefri (Universitas Sam Ratulangi, 2017)
The purpose of this study was to find out how to make probiotics with local materials and to study the effect of feed supplemented with probiotic on the growth and survival rate of freshwater pomfret fish. This study used complete randomized design with 4 treatments, each with 3 replications. The treatments consisted of A (Probiotics 1.5 mL/100 g feed), B (Probiotics 3 mL/100 g feed), C (Probiotic 4.5 mL/100 g feed) and D (control). The fish was fed treatment diet two times a day. The results showed that the highest weight and length of fish were obtained in treatment C and the lowest in treatment B. Survival rate of pomfret was quite high ranging from 96-100%.Keywords: pomfret fish, probiotic, growth, survival rate